2008
DOI: 10.1176/appi.ps.59.6.663
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Health-Related Quality of Life for Veterans With Serious Mental Illness

Abstract: Among veterans who received a diagnosis of serious mental illness from providers of the Department of Veterans Affairs, women reported substantially poorer HRQOL than men across several domains but women reported better self-perceived health. Attention to the particular needs of female veterans with serious mental illness is imperative as the numbers of female veterans continue to increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
14
1
1
Order By: Relevance
“…However, pain was still independently associated with physical health-related quality of life even after controlling for hazardous drinking. While previous evidence suggests that women are more likely to experience pain than men (Robb et al 1998; Teh et al 2008), this study also suggests that pain in particular contributes to poorer HRQOL independent of bipolar or depressive symptoms. This finding underscores the need to pay attending to physical as well and mental health symptoms among women suffering from this illness.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…However, pain was still independently associated with physical health-related quality of life even after controlling for hazardous drinking. While previous evidence suggests that women are more likely to experience pain than men (Robb et al 1998; Teh et al 2008), this study also suggests that pain in particular contributes to poorer HRQOL independent of bipolar or depressive symptoms. This finding underscores the need to pay attending to physical as well and mental health symptoms among women suffering from this illness.…”
Section: Discussioncontrasting
confidence: 76%
“…In the PRIME-MD study, HRQOL assessed using the Medical Outcomes Study SF-20 was significantly lower in women than in men, but these differences in HRQOL were no longer significant in five of six domains after controlling for mental disorder diagnoses (Linzer et al 1996). In a population of U.S. Veterans with serious mental illness, female Veterans reported lower scores on the SF-36 physical component summary, more limitations on activities of daily living, and more pain than male Veterans (Teh et al 2008). Among patients specifically diagnosed with bipolar disorder, Robb and colleagues (Robb et al 1998) found that women reported numerically lower SF-20 scores across most domains, with significant differences in pain and physical health.…”
Section: Introductionmentioning
confidence: 99%
“…(0 ¼ ''not at all'' to 4 ¼ ''extremely''), and ''During the past 4 weeks did you have a lot of energy? (0 ¼ ''none of the time'' to (Salyers, Bosworth, Swanson, et al, 2000;Teh, Kilbourne, McCarthy, et al, 2008). The Colorado Symptom Index (CSI) (Shern, Wilson, & Coen, 1994) is a self-report measure (with 10 items) of psychiatric symptoms, in which people indicate the frequency of various psychiatric symptoms they have experienced during the past month, using a 5-point Likert-type scale: 1 ¼ ''At least every day,'' 2 ¼ ''Several times a week,'' 3 ¼ ''Several times during the month,'' 4 ¼ ''Once during the month,'' and 5 ¼ ''Not at all.''…”
Section: Methodsmentioning
confidence: 99%
“…Gender as a variable can also play a role in quality of life as shown in female American veterans who scored lower than male veterans [4,9]. With this knowledge, decision-makers should take genders differences into account when formulating policies.…”
Section: Introductionmentioning
confidence: 99%